Echocardiographic indices and hospital stay among patients with acute heart failure at the Hospital Guillermo Almenara Irigoyen, 2015 - Barrantes Alarcón, Ciro (2020)
Objective: To know the association between the length of hospital stay for acute heart failure and four echocardiographic indices among inpatients in the Coronary Care Unit of the Hospital Guillermo Almenara Irigoyen. The study indices were the ratio of mitral valve inflow velocity of pulsed-wave Doppler E and mitral annular tissue velocity of pulsed-wave Doppler e' (E/e'), inferior vena cava diameter, inferior vena cava collapse rate and pulmonary artery systolic pressure. Materials and methods: A quantitative, descriptive, retrospective and correlational study was conducted with all patients hospitalized for acute heart failure during 2015. The association that the length of hospital stay has with the E/e' ratio, inferior vena cava diameter and pulmonary artery systolic pressure was analyzed using Pearson's correlation coefficient. The relationship between the length of hospital stay and the inferior vena cava collapse rate was determined using the OR. Results: The study population consisted of 65 patients whose mean age was 67.8 years and who were mainly males (61.5 %). The mean hospital stay was 5.83 days. The diagnosis of heart failure was associated with a hospital stay greater than 5 days (chi-square test). There was no association between left ventricular ejection fraction and hospital stay (OR = 1.016; 95 % CI = 0.380 - 2.717). A significant association was found between a longer hospital stay and the increase in the E/e' ratio (p = 0.002), larger inferior vena cava diameters (p = 0.006) and inferior vena cava collapse rates less than 50 % (p < 0.0000). Conclusions: The increase in the E/e' ratio, the larger inferior vena cava diameter and the inferior vena cava collapse rate less than 50 % are associated with a long hospital stay among inpatients with acute heart failure in a coronary care unit.